Similar ventral occipito-temporal cortex activations in literate and illiterate adults during the Chinese character matching task: An fMRI study - Qi, Geqi; Li, Xiujun; Yan, Tianyi; Wang, Bin; Yang, Jiajia; Wu, Jinglong; Guo, Qiyong (Neuroscience letters, 2014)
•We compared literate and illiterate vOT responses during word matching task.•Literate adults performed better than illiterate adults on the word matching task.•vOT response to words was not affected by expertise during the matching task.•The association of expertise and vOT response may depend on the task demand. Visual word expertise is typically associated with enhanced ventral occipito-temporal (vOT) cortex activation in response to written words. Previous study utilized a passive viewing task and found that vOT response to written words was significantly stronger in literate compared to the illiterate subjects. However, recent neuroimaging findings have suggested that vOT response properties are highly dependent upon the task demand. Thus, it is unknown whether literate adults would show stronger vOT response to written words compared to illiterate adults during other cognitive tasks, such as perceptual matching. We addressed this issue by comparing vOT activations between literate and illiterate adults during a Chinese character and simple figure matching task. Unlike passive viewing, a perceptual matching task requires active shape comparison, therefore minimizing automatic word processing bias. We found that although the literate group performed better at Chinese character matching task, the two subject groups showed similar strong vOT responses during this task. Overall, the findings indicate that the vOT response to written words is not affected by expertise during a perceptual matching task, suggesting that the association between visual word expertise and vOT response may depend on the task demand.